2021
DOI: 10.1002/14651858.cd013825.pub2
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-neutralising monoclonal antibodies for treatment of COVID-19

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 103 publications
0
82
0
4
Order By: Relevance
“…A Cochrane Database systematic review revealed that treatment with regdanvimab (solely based on NCT04602000 data) may decrease the risk of hospital admissions or death in outpatients with mild-to-moderate COVID-19 versus placebo [risk ratios (95% CIs) 0.45 (0.14–1.42) for 40 mg/kg; 0.56 (0.19–1.60) for 80 mg/kg] [ 19 ].…”
Section: Scientific Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…A Cochrane Database systematic review revealed that treatment with regdanvimab (solely based on NCT04602000 data) may decrease the risk of hospital admissions or death in outpatients with mild-to-moderate COVID-19 versus placebo [risk ratios (95% CIs) 0.45 (0.14–1.42) for 40 mg/kg; 0.56 (0.19–1.60) for 80 mg/kg] [ 19 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…The Cochrane Database systematic review estimated that regdanvimab treatment may increase the risk of developing grades 3–4 AEs versus placebo [risk ratios (95% CIs) 2.62 (0.52–13.12) for 40 mg/kg; 2.00 (0.37–10.70) for 80 mg/kg] [ 19 ].…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Among the patients at increased risk of their illness becoming severe, 3.1% of patients treated with Regkirona (14 out 446) were hospitalized, required supplemental oxygen or died within 28 days of treatment compared with 11.1% of patients on placebo (48 out of 434). ( Kreuzberger et al, 2021 )…”
Section: Recommended Therapeutic Agents/potential Treatmentmentioning
confidence: 99%
“…Reinforcing this idea, in clinical trials evaluating the effectiveness of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-neutralizing monoclonal antibodies for treating Covid-19 in hospitalized individuals, equivalent time-dependent treatment effects have been reported. 3 Taken together, the results of both the MOVe-OUT and MOVe-IN trials suggest that molnupiravir appears to be most effective when treatment is started early in the disease course for patients who do not require hospitalization (outpatient setting), have mild to moderate Covid-19, and are at high risk for severe disease. Unlike other drugs for Covid-19 approved by the Food and Drug Administration (FDA) for Emergency Use Authorization (EUA), molnupiravir is an orally bioavailable antiviral with excellent pharmacokinetic properties.…”
mentioning
confidence: 98%